New Mechanism by Which Human Cytomegalovirus MicroRNAs Negate the Proinflammatory Response to Infection - Andrew D. Yurochko (American Society for Microbiology, 2017)
ABSTRACT Viruses have evolved many novel mechanisms to promote infection and to mitigate the host cell response to that infection. In the article by M. H. Hancock et al. (mBio 8:e00109-17, 2017, https://doi.org/10.1128/mBio.00109-17 ), the authors describe a new mechanism by which human cytomegalovirus (HCMV) microRNAs (miRNAs; miR-US5-1 and miR-UL112-3p) negate the proinflammatory response to infection. The authors document that these two viral miRNAs downregulate the NF-κB response through direct targeting of the IKKα and IKKβ mRNAs, which in turn, through diminished IκB kinases (IKKs), block production of proinflammatory cytokines (interleukin-6 [IL-6], CCL5, and tumor necrosis factor alpha [TNF-α]). Because most signaling pathways that promote NF-κB activation and nuclear translocation ultimately converge on the activation of the IKK complex, this new study documents that HCMV can strongly dictate how infected cells respond to internal and/or external stimuli and thus positively influence the outcome of both lytic and latent infection.